Walking in the neighbourhood: Performing social citizenship in dementia. (May 2016) - Phinney, Alison; Kelson, Elizabeth; Baumbusch, Jennifer; O'Connor, Deborah; Purves, Barbara
The proliferation of community-based activity programs for people with dementia suggests an appetite for new approaches to support quality of life and well-being for this population. Such groups also have potential to promote social citizenship, although this remains poorly understood. This article presents findings from a subset of data from an ethnographic study of a community-based program for people with young onset dementia; it focuses on Paul's Club and the experiences of 12–15 members who are physically healthy, with moderate to moderately severe dementia. Analysis suggests how aspects of social citizenship are constructed and revealed through the Club's everyday practice of walking in the neighbourhood. Three major themes emerged: Keeping the focus off dementia ; Creating a place of belonging ; and Claiming a place in the community . How the group balances consideration of members' vulnerability and agency is discussed, and the article concludes with implications for future practice and research initiatives.